THE POLITICS OF RELIGION THE INVENTION OF âAGAMAâ IN INDONESIA - Hidayah, Sita (Jurnal Kawistara, 2012)
âAgamaâ (English: Religion) is a heavily loaded word in Indonesia imbued with a simplistic view that the discourse of âagamaâ is especially about morality but which is also politically motivated by power interests. The simplicity of the argument is not that it is incorrect, but the valid questions here are: âwhat the meaning of âagamaâ isas informed by ethnographies of adat communities, historical archives, media reports, and Indonesian state policies?âThis paper examines the âcondition of possibilityâ of the emergence of the discourse of âagamaâ in Indonesia. Foucaultâs theoretical framework is used to investigate the invention of âagamaâ in Indonesia.Here I limit the discussion to the historical and sociological beliefs and practices that make âagamaâ possible and focus on âagamaâ as an operational category in Indonesian politics.This paper links the discourse on âagamaâ with the discussion of citizenship. Signiïcant inïuence of the discourse of âagamaâ in the Indonesian systems of government, I argue, has become the most powerful force informing the concept of citizenship in Indonesia. The production of stateâs deïnition of the term âagamaâ was a rupture marking the construction of a new âïeld of controlâ in the way in which it creates, registers, categorizes, and controls Indonesiansâ citizenship; thus citizenship is reinforced or subverted by this speciïc meaning of âagamaâ.The formalization of âagamaâ and regularitiesof the formalized âagamaâ has consistently been appropriated to legitimate the adoption of every so often violent measures targeting religious minorities in Indonesia. This paper will also highlight the relationship between the discourse of âagamaâ and the political exclusion of religious minorities in Indonesia